Metformin alleviates the calcification of aortic valve interstitial cells through activating the PI3K/AKT pathway in an AMPK dependent way - Qiao En; Huang Zeping; Wang Yuetang; Wang Xu; Wang Wei (BMC, 2021)
Abstract Background Calcific aortic valve disease (CAVD) is the most prevalent valvular disease worldwide. However, no effective treatment could delay or prevent the progression of the disease due to the poor understanding of its pathological mechanism. Many studies showed that metformin exerted beneficial effects on multiple cardiovascular diseases by mediating multiple proteins such as AMPK, NF-κB, and AKT. This study aims to verify whether metformin can inhibit aortic calcification through the PI3K/AKT signaling pathway. Methods We first analyzed four microarray datasets to screen differentially expressed genes (DEGs) and signaling pathways related to CAVD. Then aortic valve samples were used to verify selected genes and pathways through immunohistochemistry (IHC) and western blot (WB) assays. Aortic valve interstitial cells (AVICs) were isolated from non-calcific aortic valves and then cultured with phosphate medium (PM) with or without metformin to verify whether metformin can inhibit the osteogenic differentiation and calcification of AVICs. Finally, we used inhibitors and siRNA targeting AMPK, NF-κB, and AKT to study the mechanism of metformin. Results We screened 227 DEGs; NF-κB and PI3K/AKT signaling pathways were implicated in the pathological mechanism of CAVD. IHC and WB experiments showed decreased AMPK and AKT and increased Bax in calcific aortic valves. PM treatment significantly reduced AMPK and PI3K/AKT signaling pathways, promoted Bax/Bcl2 ratio, and induced AVICs calcification. Metformin treatment ameliorated AVICs calcification and apoptosis by activating the PI3K/AKT signaling pathway. AMPK activation and NF-κB inhibition could inhibit AVICs calcification induced by PM treatment; however, AMPK and AKT inhibition reversed the protective effect of metformin. Conclusions This study, for the first time, demonstrates that metformin can inhibit AVICs in vitro calcification by activating the PI3K/AKT signaling pathway; this suggests that metformin may provide a potential target for the treatment of CAVD. And the PI3K/AKT signaling pathway emerges as an important regulatory axis in the pathological mechanism of CAVD.